The effects of nattokinase supplementation on collagen–epinephrine closure time, prothrombin time and activated partial thromboplastin time in nondiabetic and hypercholesterolemic subjects. Issue 5 (9th May 2019) - Yoo, Hye Jin; Kim, Minkyung; Kim, Minjoo; Lee, Ayoung; Jin, Chunmei; Lee, Sung Pyo; Kim, Tae Su; Lee, Sang-Hyun; Lee, Jong Ho
Abstract : For 8 weeks, individuals who consumed nattokinase, considered one of the most active functional ingredients found in natto, showed improved hemostatic factors. Abstract : The aim of this study was to investigate whether supplementation with nattokinase, which is considered one of the most active functional ingredients found in natto, alters hemostatic factors. Subjects presenting with hypercholesterolemia (serum cholesterol: 200–280 mg dL −1 ) were randomly divided into nattokinase and placebo groups ( n = 50, respectively). No significant between-group differences were found at baseline in collagen–epinephrine closure time (C-EPI CT), prothrombin time (PT), or activated partial thromboplastin time (aPTT). After 8 weeks of treatment, the nattokinase group exhibited significant increases in C-EPI CT, PT, and aPTT. The nattokinase group showed significantly greater increases in C-EPI CT ( P = 0.001) and aPTT ( P = 0.016) than the placebo group. Moreover, at 8 weeks, the nattokinase group showed a significantly higher C-EPI CT than the placebo group ( P = 0.001). Additionally, a significant correlation between PT and aPTT was observed ( r = 0.491, P < 0.001). In conclusion, nattokinase supplementation was associated with prolonged C-EPI CT and aPTT in nondiabetic and borderline-to-moderate hypercholesterolemic subjects.